Structural health monitoring using piezoelectric materials - Wee, Kim Hwee. (2013)
There is a rising need for a structural health monitoring (SHM) method for civil and building structures all around the world nowadays. Amongst the various types of sensors available in the market used to monitor structural health, the Piezoelectric (PZT) transducer has been constantly in use and considered one of the more promising sensors because of its various advantages such as being cost effective, remote monitoring, able to be installed in very inaccessible places and being a method of non-destructive evaluation.